2018
DOI: 10.20944/preprints201807.0467.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biases Inherent in Studies of Coffee Consumption in Early Pregnancy and the Risks of Subsequent Events

Abstract: Consumption of coffee by women early in their pregnancy has been viewed as potentially increasing the risk of miscarriage, low birth weight, and childhood leukemias. Many of these reports of epidemiologic studies have not acknowledged the potential biases inherent in studying the relationship between early-pregnancy-coffee consumption and subsequent events. I discuss five of these biases, recall bias, misclassification, residual confounding, reverse causation, and publication bias. Each might account for claim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 121 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…That is, it is generally recognized by epidemiologists that, when asking mothers to recall what they may have ingested during pregnancy after giving birth to a child with a birth defect or disease, they will try to find a cause. For this reason, an alternative study design is for both the case and control populations to have adverse conditions manifested; otherwise, there is a high likelihood of recall bias [ 28 ]. Another stronger study design option would be a nested case-control design with prospective assessment of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…That is, it is generally recognized by epidemiologists that, when asking mothers to recall what they may have ingested during pregnancy after giving birth to a child with a birth defect or disease, they will try to find a cause. For this reason, an alternative study design is for both the case and control populations to have adverse conditions manifested; otherwise, there is a high likelihood of recall bias [ 28 ]. Another stronger study design option would be a nested case-control design with prospective assessment of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…25,39,71 Furthermore, any association between caffeine and miscarriage is likely to be confounded by the fact that a healthy pregnancy is associated with nausea and vomiting (due to pregnancy hormones), which in turn may reduce caffeine consumption. 72 Our literature searches found that night shift work is associated with an increased risk of miscarriage (aOR 1•43;…”
Section: Lifestyle Risk Factorsmentioning
confidence: 98%
“…Large twin studies conducted in northern European populations report shared genetic factors in explaining the co-occurrence of smoking and caffeine intake, including especially caffeine intake derived from coffee drinking [42]. Part of this may be due to the fact that coffee intake is counter-indicated in some medical conditions and this may be difficult to disentangle in cohort studies when the reasons for no/reduced coffee intake is not known [7,23,48]. Mechanistic studies suggest that a protective association between coffee intake and RCC is biologically plausible.…”
Section: Discussionmentioning
confidence: 99%